Search for new physics using QUAERO: a general interface to D0 event data. - Abazov, V; Abbott, B; Abdesselam, A; Abolins, M; Abramov, V; Acharya, B; Adams, D; Adams, M; Ahmed, SN; Alexeev, G; Alves, G; Amos, N; et al. (2001)
We describe QUAERO, a method that (i) enables the automatic optimization of searches for physics beyond the standard model, and (ii) provides a mechanism for making high energy collider data generally available. We apply QUAERO to searches for standard model WW, ZZ, and t t macro production, to searches for these objects produced through a new heavy resonance, and to the first direct search for W'-->WZ. Through this interface, we make three data sets collected by the D0 experiment at square root of [s] = 1.8 TeV publicly available.